Alpha-glucosidase inhibitory activity of the combination of Caesalpinia sappan L. and Garcinia mangostana extract - Nina Artanti, Indah Dwiatmi Dewijanti, Dian Muzdalifah, Anjar Windarsih, Suratno Suratno, Sri Handayani (Journal of Applied Pharmaceutical Science, 2023)
Garcinia mangostana (Gm) and Caesalpinia sappan (Cs) are traditional food used for health supplements. Nevertheless, the synergistic effect of the combinations has never been studied for antidiabetic supplements. This study aimed to evaluate the synergistic α-glucosidase activity of Gm pericarp and Cs heartwood combination extracts. Both plants were extracted with ethanol and water. The total flavonoid content was measured by colourimetric assay. The α-glucosidase inhibitory assay was used to measure the α-glucosidase inhibitory activity of extracts. Synergistic effects were analyzed by calculating the combination index (CI). Targeting compounds inside the extracts were detected using liquid chromatography high-resolution mass spectrometry. Protein-ligand interaction was analyzed using Yet Another Scientific Artificial Reality Application, Protein-Ligand Ant System, and Ligplot+ software. The total flavonoid content of Cs aqueous extract was higher than Gm, while the ethanol extract had similar results. The α-glucosidase inhibitory activity of both extracts was in line with their total flavonoid content. The ethanol extracts showed higher activity compared to the aqueous extracts. The combination of both extracts revealed synergistic inhibitory effects on α-glucosidase activity (CI < 1). Flavonoid compounds of Gm and Cs extracts revealed their affinity with the acarbose active site in the α-glucosidase enzyme. Thus, the combination of Gm and Cs extract can be developed as a potential herbal supplement to prevent and manage diabetes mellitus.
Keywords: Þ-glucosidase activity, Caesalpinia sappan heartwood, Garcinia mangostana pericarp, natural product, synergist